TRAÇADO DE REDE DE FLUXO DE ÁGUA SUBTERRÂNEA UTILIZANDO O PROGRAMA GFLOW1 E O SOFTWARE MAPLE 6.0 - Gomes, Carisia Carvalho; Castro, Marco Aurélio Holanda de (Águas Subterrâneas, 2001)
Resumo não disponível.